2022
DOI: 10.1002/advs.202202642
|View full text |Cite
|
Sign up to set email alerts
|

NNMT‐DNMT1 Axis is Essential for Maintaining Cancer Cell Sensitivity to Oxidative Phosphorylation Inhibition

Abstract: Lacking a clear understanding of the molecular mechanism determining cancer cell sensitivity to oxidative phosphorylation (OXPHOS) inhibition limits the development of OXPHOS‐targeting cancer treatment. Here, cancer cell lines sensitive or resistant to OXPHOS inhibition are identified by screening. OXPHOS inhibition‐sensitive cancer cells possess increased OXPHOS activity and silenced nicotinamide N‐methyltransferase (NNMT) expression. NNMT expression negatively correlates with OXPHOS inhibition sensitivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…For example, loss of LUC7L2 and U1 snRNP subunits shifts the energy metabolism from glycolysis to OXPHOS 60 . The recent study also demonstrated that cancer cells relying on more OPXHOS are highly expressing DNMT1 and lowly expressing NNMT, by genetically manipulating the expression of NNMT and DNMT1, the sensitivity to OXPHOS inhibitors are changed 61 . Overexpression of NNMT and knockdown of DNMT1 change OXPHOS-inhibition sensitive cell line to be resistant ones, indicating their energy resource reliance shifted from OXPHOS to glycolysis 61 .…”
Section: Mitochondrial Function In Cancer Cell Metabolismmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, loss of LUC7L2 and U1 snRNP subunits shifts the energy metabolism from glycolysis to OXPHOS 60 . The recent study also demonstrated that cancer cells relying on more OPXHOS are highly expressing DNMT1 and lowly expressing NNMT, by genetically manipulating the expression of NNMT and DNMT1, the sensitivity to OXPHOS inhibitors are changed 61 . Overexpression of NNMT and knockdown of DNMT1 change OXPHOS-inhibition sensitive cell line to be resistant ones, indicating their energy resource reliance shifted from OXPHOS to glycolysis 61 .…”
Section: Mitochondrial Function In Cancer Cell Metabolismmentioning
confidence: 97%
“…The recent study also demonstrated that cancer cells relying on more OPXHOS are highly expressing DNMT1 and lowly expressing NNMT, by genetically manipulating the expression of NNMT and DNMT1, the sensitivity to OXPHOS inhibitors are changed [61]. Overexpression of NNMT and knockdown of DNMT1 change OXPHOS-inhibition sensitive cell line to be resistant ones, indicating their energy resource reliance shifted from OXPHOS to glycolysis [61]. In the process of energy metabolic switch, the M2 isoform of pyruvate kinase (PKM2, a rate-limiting enzyme in glycolysis) interacts with the key regulator of mitochondrial fusion protein MFN2 to promote the mitochondria fusion and OXPHOS, meanwhile attenuate glycolysis [62], consistently, the activation of MFN2 interacting with PFK1 mediate PFK1 degradation and therefore suppresses glycolysis [63].…”
Section: The Interplay Between Mitochondria and Glycolysismentioning
confidence: 98%
“…Reduced histone methylation is a consequence of NNMT's ability to catalyze the methylation of pyridine compounds with S-5′-adenosyl-l-methionine. NNMT is widely expressed in the human body, especially in organs and tissues such as the liver, kidneys, brain, lungs, and adipose tissue, where it is expressed at higher levels [ 48 , 49 ]. The activity and expression levels of NNMT are regulated by various factors, including genetic variations, environmental factors, and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…For many types of malignancies, the low early detection rate is an obstacle to improved cancer control; 249,250 therefore, efforts to identify novel diagnostic markers are valuable. 251 CD47 has been demonstrated as a diagnostic biomarker for a variety of cancers. It is an innate immune checkpoint and is closely related to the survival in different cancers.…”
Section: Phagocytosis Checkpoints In Diseases and The Tumor Microenvi...mentioning
confidence: 99%